2008
DOI: 10.1016/j.bbi.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of inflammation in response to anthracycline-based chemotherapy for breast cancer

Abstract: Although chemotherapy for breast cancer can increase inflammation, few studies have examined predictors of this phenomenon. This study examined potential contributions of demographics, disease characteristics, and treatment regimens to markers of inflammation in response to chemotherapy for breast cancer. Thirty-five women with stage I -III-A breast cancer (mean age 50 years) were studied prior to cycle 1 and prior to cycle 4 of anthracycline-based chemotherapy. Circulating levels of inflammatory markers with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 37 publications
5
43
0
1
Order By: Relevance
“…14 Some of the toxic effects of chemotherapy drugs are caused by the increased production of infl ammatory mediators. 15,16 Consistent with previous studies, we demonstrated that AraC caused infl ammatory cell Fig. 1A-D. The effect of sodium zinc dihydrolipoylhistidinate against cytosine arabinoside-induced alopecia.…”
Section: Discussionsupporting
confidence: 79%
“…14 Some of the toxic effects of chemotherapy drugs are caused by the increased production of infl ammatory mediators. 15,16 Consistent with previous studies, we demonstrated that AraC caused infl ammatory cell Fig. 1A-D. The effect of sodium zinc dihydrolipoylhistidinate against cytosine arabinoside-induced alopecia.…”
Section: Discussionsupporting
confidence: 79%
“…Chemotherapy can induce the release of vascular endothelial growth factor, interleukin-6 (IL-6), and other cytokines (Mills et al 2008;. Increased level of circulating pro-inflammatory cytokines is highly associated with fatigue (Rich et al 2005;Schubert et al 2007;Mills et al 2008;.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that clinical outcome in breast cancer patients is associated with elevations of proinflammatory serum biomarkers after taxane treatment (47)(48)(49)(50). Tumor cell exposure to anthracyclines and some platin drugs has been shown to induce immunostimulatory apoptosis and presentation of damage-associated molecular patterns, including calreticulin, heat-shock proteins, and high-mobility group box 1 proteins, before, during, or after apoptosis (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%